Führer des Grossen Oktobers!
soziale Fragen;Kultur und Religion;Kulturpolitik;Gedächtnisfeier;Jubiläum soziale Fragen;Kultur und Religion;Kultur;Regionalkultur politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Sozialismus